An Improved Control Method for Direct Torque Control Based on Sliding Mode Control - Thi-Hong-Huong Ngo,; Minh-Tam Nguyen,; Vinh-Quan Nguyen, (Journal of Technical Education Science, 2024)
This paper presents an improved method of direct torque control (DTC) for three–phase asynchronous motors with squirrel cage rotors. The improved method of DTC uses three sliding mode controllers to control torque and flux independently. From simulation and experimentation in real time RT, using Sim Power Systems of matlab-simulink through RT-LAB compiler, hardware simulation algorithm in HIL- Hardware-in-the-Loop by OPAL-RT device for the three-phase asynchronous induction motor, this is the new algorithm presented in the article. The three-phase asynchronous induction motor 1-hp, 150 rad/s with a three-phase three-level cascade inverter, the results show the estimated speed and the good tracking speed according to the value set at a frequency varying from the lowest 3 rad/s to the highest 150 rad/s, and the system remains stable when the stator and rotor resistance changes up to 1.5 times the initial value in the presence of noise. Simulation during execution, so simulation results and experimental results are very consistent. On the other hand, using a multi-level inverter with the new PM modulation algorithm increases the system's sustainability compared to the two-level inverter used in previously published articles. The results also show that using a sliding surface with a nonlinear function that has been proven to be Lyapunov stable significantly reduces the moment chattering phenomenon compared to previous algorithms using DTC control.